2021
DOI: 10.3389/fbioe.2021.639409
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Andrographolide in poly(lactide-co-glycolide) Nanoparticles: Formulation Optimization and in vitro Efficacy Studies

Abstract: Andrographolide is a potential chemopreventive and chemotherapeutic agent that suffers from poor aqueous solubility. Encapsulation in poly(lactide-co-glycolide) (PLGA) nanoparticles can overcome solubility issues and enable sustained release of the drug, resulting in improved therapeutic efficacy. In this study, andrographolide was encapsulated in PLGA nanoparticles via emulsion solvent evaporation technique. Effect of various formulation parameters including polymer composition, polymer molecular weight, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 59 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Recent pharmaceutical studies were aimed at improving the poor bioavailability and solubility of andrographolide via appropriate delivery systems. [ 26 , 27 ] However, appropriate chemical modifications of andrographolide could be an even better option to overcome such issues. Therefore, three different amide derivatives ( 16 a – 16 c ) were synthesized from linear aliphatic or aromatic amines.…”
Section: Resultsmentioning
confidence: 99%
“…Recent pharmaceutical studies were aimed at improving the poor bioavailability and solubility of andrographolide via appropriate delivery systems. [ 26 , 27 ] However, appropriate chemical modifications of andrographolide could be an even better option to overcome such issues. Therefore, three different amide derivatives ( 16 a – 16 c ) were synthesized from linear aliphatic or aromatic amines.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Yen, with his colleagues, experimented and found that silver-loaded andrographolide nanoparticles enhance bioavailability by 594.3% and are efficient against pro-inflammatory cytokines (eg, IL-1β, IL-6 and TNF-α) and the chemokine IL-8 [ 106 ]. Similarly, in an in vitro breast cancer model, encapsulating andrographolide in PLGA nanoparticles helps to overcome solubility difficulties and allowed for continuous drug release [ 107 ]. The use of hydroxypropyl-β-cyclodextrin (HP-β-CD) formulated andrographolide molecule increased its bioavailability by 1.19 percent [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive research is to be done on its administration to higher animals and humans, and cytotoxicity limits should be checked. Moreover, studies have been conducted on the drug delivery system of andrographolide conjugated with microparticles and nanoparticles [132,133]. In the form of vesicles, nanoemulsions, micelles, and gold nanoparticles, andrographolide is used to treat various disorders.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%